Phenotyping patients with chronic obstructive pulmonary disease and heart failure - Peter Moritz Becher; Felix Lindberg; Lina Benson; Camilla Hage; Ulf Dahlström; Stephan Rosenkranz; Francesco Cosentino; Giuseppe M.C. Rosano; Stefan Blankenberg; Paulus Kirchhof; Frieder Braunschweig; Lars H. Lund; et al. (ESC Heart Failure)
Abstract Aims Chronic obstructive pulmonary disease (COPD) and heart failure (HF) are prevalent comorbidities associated with significant morbidity/mortality. We assessed prevalence of, patient profiles and outcomes associated with COPD across the ejection fraction (EF) spectrum. Methods HF patients enrolled in the Swedish HF registry between 2005 and 2021 were considered. Multivariable logistic regression models were fitted to assess patient characteristics independently associated with COPD and Cox regression models for investigating the associations between COPD and outcomes, that is, morbidity/mortality. Results Among 97 904 HF patients, COPD prevalence was 13%, highest in HF with preserved EF [HFpEF: 16%, HF with mildly reduced EF (HFmrEF): 12%, HF with reduced EF (HFrEF): 11%]. Key patient characteristics independently associated with a diagnosis of COPD included higher EF, female sex, smoking, obstructive sleep disorder, peripheral artery disease, a lower educational level, more severe HF, more likely mineralocorticoid receptor antagonist and diuretic use but less likely use of angiotensin‐converting enzyme inhibitors/angiotensin receptor blockers/angiotensin‐receptor‐neprilysin inhibitors (not in HFrEF), beta‐blockers, HF device therapies, and follow‐up in HF nurse‐led clinics. COPD was independently associated with a 15% higher risk of cardiovascular (CV) death/HF hospitalization [hazard ratio: 1.15 (95% confidence interval: 1.11–1.18)], CV death, non‐CV death, all‐cause death and HF hospitalizations, regardless of EF. Conclusions COPD was present in every eight patient with HF, and more common with preserved EF. Patients with COPD had more severe HF, heavier comorbidity burden and worse morbidity/mortality regardless of EF. Our results call for improved diagnostic and management strategies in patients with HF and COPD.